2008
DOI: 10.1167/iovs.08-2142
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Retinal Vascular Narrowing in Glaucomatous Eyes in an Asian Population

Abstract: These findings support an association of narrower retinal arteriolar and venular caliber changes with glaucomatous optic neuropathy, independent of intraocular pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
86
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 43 publications
14
86
2
3
Order By: Relevance
“…In an Asian population, evidence of retinal vascular narrowing was recently reported in glaucomatous eyes after adjusting for age [65]. These findings support an association of narrower retinal arteriolar and venular caliber changes with glaucomatous optic neuropathy independent of IOP after adjusting for age [65]. These findings are consistent with two other populationbased studies: the Blue Mountains Eye Study [66] and the Fig.…”
Section: Age-related Ocular Blood Flow and Vascular Changes In Glaucomasupporting
confidence: 90%
“…In an Asian population, evidence of retinal vascular narrowing was recently reported in glaucomatous eyes after adjusting for age [65]. These findings support an association of narrower retinal arteriolar and venular caliber changes with glaucomatous optic neuropathy independent of IOP after adjusting for age [65]. These findings are consistent with two other populationbased studies: the Blue Mountains Eye Study [66] and the Fig.…”
Section: Age-related Ocular Blood Flow and Vascular Changes In Glaucomasupporting
confidence: 90%
“…The Singapore Malay Eye Study showed that both arteriolar and venular narrowing were associated with the presence of glaucoma. 49 The Beijing Eye Study showed that a narrower arteriolar caliber was associated with a higher prevalence of glaucoma. 50 Furthermore, in the Blue Mountains Eye Study, Kawasaki et al 51 reported that during the 10-year follow-up period, narrowing of the retinal arterioles occurred before the development of earlystage glaucoma and was associated with a long-term risk of OAG.…”
Section: Vessel Narrowing In Glaucomamentioning
confidence: 99%
“…[3][4][5][6] Decreased retinal perfusion has also been demonstrated angiographically in glaucoma patients using fluorescein angiography.…”
mentioning
confidence: 99%
“…tudies have shown that peripapillary retinal blood flow 1,2 and retinal vessel caliber 3,4 are reduced in glaucoma patients compared with healthy subjects, using laser Doppler flowmetry, 1 Doppler optical coherence tomography (OCT), 2 and measurements of retinal vessel caliber. [3][4][5][6] Decreased retinal perfusion has also been demonstrated angiographically in glaucoma patients using fluorescein angiography.…”
mentioning
confidence: 99%